A needs analysis of english proficiency at a State Vocational Institute: A case study - Setiyowati, Menik; Ningsih, Harni Kartika (Institute of Computer Science (IOCS), 2025)
This study reports on the result of a needs analysis for English proficiency. in the Instrumentation program at State Vocational Institute A. It is done to improve syllabus alignment with professional demands. The primary objective of this paper to identify gaps in the existing syllabus by analyzing responses from 27 fifth-semester students who had completed English courses in their third semester and 50 alumni working at the field. Using a qualitative descriptive method, the case study collected data through a structured questionnaire that focused on identifying and addressing practical challenges in professional English usage. Results from students' responses revealed that while foundational English skills, such as understanding instructions and interacting in class, were rated positively, students experienced difficulties in technical writing, oral presentations, and expressing opinions related to their field. These challenges indicate that the existing syllabus may not fully equip students with the language skills required to perform complex tasks in professional contexts. Alumni responses further supported these findings, highlighting inadequacies in practical communication skills, especially in technical reporting and workplace interactions. The study identified emerging gaps between the English proficiency of both students and alumni and the demands of academic and professional environments. These findings suggest the need for curriculum revisions to address the specific linguistic challenges faced by students and graduates so as to ensure that future revisions align closely with workplace expectations.